Upper bound of fractional differential operator related to univalent functions - Kilicman, Adem; W. Ibrahim, Rabha; E. Abdulnaby, Zainab (Springer, 2016)
In this article, we defined the generalized fractional differential Tremblay operator in the open unit disk that by usage the definition of the generalized Srivastava–Owa operator. In particular, we established a new operator denoted by Θβ,τ,γz based on the normalized generalized fractional differential operator and represented by convolution product. Moreover, we studied the coefficient criteria of univalence, starlikeness and convexity for the last operator mentioned.